1997
DOI: 10.1073/pnas.94.12.6019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenase genes from Rhizobium leguminosarum bv. viciae are controlled by the nitrogen fixation regulatory protein NifA

Abstract: Rhizobium leguminosarum bv. viciae expresses an uptake hydrogenase in symbiosis with peas (Pisum sativum) but, unlike all other characterized hydrogenoxidizing bacteria, cannot express it in free-living conditions. The hydrogenase-specific transcriptional activator gene hoxA described in other species was shown to have been inactivated in R. leguminosarum by accumulation of frameshift and deletion mutations. Symbiotic transcription of hydrogenase structural genes hupSL originates from a ؊24͞؊12 type promoter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 47 publications
(51 reference statements)
3
87
1
Order By: Relevance
“…The increased levels of hydrogenase activity in strains with multiple copies of HupF or HupK are consistent with the presence of these proteins in hydrogenase systems from aerobic bacteria (27). Our laboratory had previously shown that the R. leguminosarum hydrogenase system is expressed under symbiotic conditions in a NifA-dependent way that links its expression to that of nitrogenase (23,61). It is thus conceivable that the levels of expression of HupK and HupF had been adjusted to the needs of a virtually anaerobic habitat such as the legume nodule (55) and might become limiting when the system is expressed under higher oxygen tensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased levels of hydrogenase activity in strains with multiple copies of HupF or HupK are consistent with the presence of these proteins in hydrogenase systems from aerobic bacteria (27). Our laboratory had previously shown that the R. leguminosarum hydrogenase system is expressed under symbiotic conditions in a NifA-dependent way that links its expression to that of nitrogenase (23,61). It is thus conceivable that the levels of expression of HupK and HupF had been adjusted to the needs of a virtually anaerobic habitat such as the legume nodule (55) and might become limiting when the system is expressed under higher oxygen tensions.…”
Section: Discussionmentioning
confidence: 99%
“…viciae the genetic determinants involved in the biosynthesis of the hydrogenase are clustered in the symbiotic plasmid and include 18 genes (hupSLCDEFGHIJKhypABFCDEX) closely linked and transcribed in the same direction (22). Symbiotic expression of this system is co-regulated with the nitrogenase genes through NifA, the master regulator of nitrogen fixation (23). To facilitate the study of the mechanisms involved in the biosynthesis of hydrogenase in R. leguminosarum, the NifA-dependent hupSL promoter was replaced by the Fnr-dependent fixN promoter, allowing the expression of hydrogenase in microaerobic vegetative cells (24).…”
mentioning
confidence: 99%
“…This is also an exceptional case; usually enhancer-binding transcription factors activate σ 54 -dependent RNA polymerase, as is the case for H 2 ase genes in R. eutropha (Römermann et al, 1989), T. roseopersicina (Colbeau et al, 1994) and B. japonicum (Black and Maier, 1995). R. leguminosarum contains an inactive pseudo-hoxA gene; the expression of H 2 ase occurs only during symbiotic growth (Brito et al, 1997). By using native acrylamide gel electrophoresis, direct interaction between HupUV/HoxBC and HupT/HoxJ proteins has been demonstrated for R. capsulatus (Elsen et al, 2003) and R. eutropha ).…”
Section: Molecular Biology Of Microbial Hydrogenases 171mentioning
confidence: 99%
“…However, in this bacterium, NifA activates directly H 2 ase expression by binding to an upstream activating sequence (UAS) of the promoter region of the structural hupSL genes. This promoter also binds the global regulator IHF and is transcribed by a σ 54 -RNA polymerase (Brito et al, 1997). Moreover, the Fnr-like protein, FnrN, indirectly activates H 2 ase expression by binding to the σ 70 -dependent promoter of hyp genes (Hernando et al, 1995), which are expressed in vegetative cells.…”
Section: ) O 2 Regulationmentioning
confidence: 99%
“…Although several transcriptional units were initially defined by symbiotic complementation analysis (Leyva et al, 1990;Hidalgo et al, 1992), only two major promoters have been characterized within this gene cluster. First, a NifA-dependent 224/212-type promoter (P 1 ), responsible for symbiotic activation of at least the hydrogenase structural genes hupSL, was identified upstream of hupS Brito et al, 1997). This NifA-dependent promoter constrains the expression of hydrogenase activity to symbiotic cells, and results in a temporal and spatial co-expression of nitrogenase and hydrogenase structural genes in pea nodules (Brito et al, 1995).…”
Section: Introductionmentioning
confidence: 99%